The Possibility of Conducting Experiments on Animals. Moral Theologian’s Reflections - Smykowski, Krzysztof (Studia Ecologiae et Bioethicae, 2015)
The Catholic moral theology acknowledges a person’s right to use animals in compliance with their nature while putting the emphasis on the obligation to treat them with proper sensitivity and kindness. This right includes the possibility to conduct experiments on animals. Such experiments are allowed after meeting a range of conditions. Justifiable hopes for scientific development or for achieving practical goals are required. Also, the number of used animals should be limited and the pain and stress the animals feel ought to be minimized. The right balance should be maintained between those factors. Moreover, moral theology elevates the value of intentions, i.e., the objective for which the test results will be used. It can modify the moral classification of experiments, which on their own are good or neutral.